Photodynamic therapy improves the clinical efficacy of advanced colorectal cancer and recruits immune cells into the tumor immune microenvironment - Gu, Baohong; Wang, Bofang; Li, Xuemei; Feng, Zedong; Ma, Chenhui; Gao, Lei; Yu, Yang; Zhang, Jing; Zheng, Peng; Wang, Yunpeng; Li, Haiyuan; Zhang, Tao; et al. (Frontiers in Immunology, 2022)
Objective: Although photodynamic therapy (PDT) has been proven effective in various tumors, it has not been widely used as a routine treatment for colorectal cancer (CRC), and the characteristics of changes in the tumor microenvironment (TME) after PDT have not been fully elucidated. This study evaluated the efficacy of PDT in patients with advanced CRC and the changes in systemic and local immune function after PDT. Methods: Patients with stage Ⅲ-Ⅳ CRC diagnosed in our hospital from November 2020 to July 2021 were retrospectively analyzed to compare the survival outcomes among each group. Subsequently, short-term efficacy, systemic and local immune function changes, and adverse reactions were assessed in CRC patients treated with PDT. Results: A total of 52 CRC patients were enrolled in this retrospective study from November 2020 to July 2021, and the follow-up period ended in March 2022. The overall survival (OS) of the PDT group was significantly longer than that of the non-PDT group (p=0.006). The objective response rate (ORR) and disease control rate two months after PDT were 44.4% and 88.9%, respectively. Differentiation degree (p=0.020) and necrosis (p=0.039) are two crucial factors affecting the short-term efficacy of PDT. The systemic immune function of stage Ⅲ patients after PDT decreased, whereas that of stage Ⅳ patients increased. Local infiltration of various immune cells such as CD3+ T cells, CD4+ T cells, CD8+ T cells, CD20+ B cells and macrophages in the tumor tissue were significantly increased. No severe adverse reactions associated with PDT were observed. Conclusion: PDT is effective for CRC without significant side effects according to the available data. It alters the tumor microenvironment by recruiting immune cells into tumor tissues.